Efficient Randomized Response Model Tailored for Estimating Highly Sensitive Characteristics - Aboalkhair, Ahmad (Statistics, Optimization & Information Computing, 2025)
When broaching extremely delicate subjects, individuals might offer inadequate or dishonest revelations, jeopardizing data precision. To counteract this challenge, this research proposes a new and effective randomized response structure crafted to enhance the assessment of highly sensitive characteristics. The proposed framework enhances Aboalkhair’s (2025) model, which has emerged as a viable substitute for Mangat’s frameworks. This investigation assesses the scenarios where the proposed method performs better than Mangat's method. Through theoretical scrutiny and numerical simulations—taking into consideration partial honest disclosures—the outcomes showcase the model's heightened effectiveness. Furthermore, the article quantifies the level of privacy safeguarding provided by this innovative approach.